PENGARUH KEPEMILIKAN MANAJEMEN, KEPEMILIKAN PUBLIK, TINGKAT LEVERAGE, DAN TINGKAT PROFITABILITAS TERHADAP RISK MANAGEMENT DISCLOSURE (PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Roberto .; Malem Ukur Tarigan (Universitas Kristen Krida Wacana, 2013)
AbstractThis study aims to analyze wheter there is influence between ownership structure, leverage and profitability mechanisms on the level of Risk Management disclosure on manufacturing companies listed in Indonesia Stock Exchange in 2009-2011. The samples used in this study were 28 companies. Data used are secondary data, such as financial statements that have been published over the years of research. The dependent variable in this study is the level of Risk Management disclosure in the annual reports of companies listed on the Indonesia Stock Exchange in 2009-2011, while the independent variables include managerial ownership, public ownership, leverage degree and the profitability degree. Results showed the impact of leverage degree is sigificant. As for the managerial ownership, public ownership and profitability degree showed that there was no significant effect on the level of Risk Management disclosure on manufacturing companies listed in Indonesia Stock Exchange in 2009-2011.Keywords: Managerial Ownership, Public Ownership, Leverage Degree, Profitability Degree, Risk Management Disclosure.